Konseling gizi fertilitas terhadap pengetahuan, sikap, asupan makronutrien, dan berat badan pasangan program bayi tabung - Aritonang, Sonia Marlaba; Mahdiah, Mahdiah; Doloksaribu, Tetty Herta; Doloksaribu, Lusyana Gloria (Jurnal Gizi Klinik Indonesia, 2024)
The effect of fertility nutrition counseling on knowledge, attitude, macronutrient intake, and body weight couple in IVF programBackground: Based on PERFITRI (2017) shows 1,712 men and 2,055 women experiencing infertility. One of the factors that influences infertility is nutritional status. Overweight and underweight will affect conception delays. Body weight is influenced by nutritional knowledge, attitudes and food intake. Efforts to increase knowledge and attitudes can be done through nutritional counseling. Objective: This study aimed to analyze the effect of nutritional counseling on knowledge, attitudes, macronutrient intake, and weight of In Vitro Fertilization (IVF) couples at Halim Fertility Center. Methods: This research was a quasi-experiment with a one group pre-post test design. The study population was all married couples who were registered for nutritional counseling for the IVF program in January-February 2023 with a sample of 43 married couples. Data analysis used the T-dependent test and the Wilcoxon test. Results: The average value of knowledge and attitudes increased with an increase in the husband’s knowledge score of 37,70 and the wife’s score 29,95 and an increase in the husband’s attitude score of 19,30 and the wife’s score of 12,79. There was a decrease in the energy intake of the husband 10,23% and the wife 7,49%, the husband's fat intake was 35,69% and the wife was 28,62%, husband's carbohydrate intake was 9,45% and the wife was 12,90%. Protein intake increased 54,31% for husbands and 55,84% for wives. The average value of body weight decreased by 2,51 kg for husbands and 1,85 kg for wives. Conclusions: There is an effect of nutritional counseling on knowledge, attitudes, macronutrient intake and weight of IVF couples (p-value=0.000).